2019
DOI: 10.1152/ajprenal.00551.2018
|View full text |Cite
|
Sign up to set email alerts
|

Targeted renal knockdown of Na+/H+exchanger regulatory factorSip1produces uric acid nephrolithiasis inDrosophila

Abstract: Nephrolithiasis is one of the most common kidney diseases, with poorly understood pathophysiology, but experimental study has been hindered by lack of experimentally tractable models. Drosophila melanogaster is a useful model organism for renal diseases because of genetic and functional similarities of Malpighian (renal) tubules with the human kidney. Here, we demonstrated function of the sex-determining region Y protein-interacting protein-1 ( Sip1) gene, an ortholog of human Na+/H+ exchanger regulatory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Flies fed the 20%S -H 2 O diet exhibited a strongly darkened tubule phenotype, which was fully rescued by water supplementation (Figures 5B and 5C). These dark deposits were intraluminal concretions suggestive of uric acid accumulation (Ghimire et al, 2019). Therefore, we assayed uric acid content biochemically from whole flies (Figure 5D) and dissected tubules (Figure S5B), which was significantly elevated on the 20%S diet ($2-and $4-fold, respectively) and again fully restored to the 5%S control baseline by water supplementation.…”
Section: Effects Of a High-sugar Diet On Stress Responses And Gut Physiologymentioning
confidence: 98%
“…Flies fed the 20%S -H 2 O diet exhibited a strongly darkened tubule phenotype, which was fully rescued by water supplementation (Figures 5B and 5C). These dark deposits were intraluminal concretions suggestive of uric acid accumulation (Ghimire et al, 2019). Therefore, we assayed uric acid content biochemically from whole flies (Figure 5D) and dissected tubules (Figure S5B), which was significantly elevated on the 20%S diet ($2-and $4-fold, respectively) and again fully restored to the 5%S control baseline by water supplementation.…”
Section: Effects Of a High-sugar Diet On Stress Responses And Gut Physiologymentioning
confidence: 98%
“…(C) Overdose dietary phosphate (Pi) uptake up-regulates the expression of Pi transporter MFS2 via bnl/btl/MFS2 pathway, results in the increase of lumen Pi concentration, and CaPi stone formation.
Figure 3 The biosynthesis pathways of (A) oxalate [ 36 , 37 , 63 ](B) uric acid [ 40 ]. Compounds in the green boxes are common lithogenic agents for CaOx kidney stone models.
…”
Section: The Establishment Of Fruit Fly Kidney Stones Modelsmentioning
confidence: 99%
“… The biosynthesis pathways of (A) oxalate [ 36 , 37 , 63 ](B) uric acid [ 40 ]. Compounds in the green boxes are common lithogenic agents for CaOx kidney stone models.…”
Section: The Establishment Of Fruit Fly Kidney Stones Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one such case, the product of the Drosophila gene prestin was shown to transport oxalate in tubules, and knockdown of prestin expression in the tubules reduced stone formation (Hirata et al 2010(Hirata et al , 2012. In another study, Drosophila mutants of the gene NHERF/Sip1 were found to carry a massive stone burden of uric acid crystals (Ghimire et al 2019). The loss of naturally occurring uric acid crystals was also used as a screen to identify those V-ATPase subunits that formed the plasma membrane proton pump in Drosophila tubule principal cells (Allan et al 2005).…”
Section: Modeling Disease Processesmentioning
confidence: 99%